2019
DOI: 10.1016/j.celrep.2019.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Presentation of High-Affinity Immune Complexes in Germinal Centers Can Explain How Passive Immunization Improves the Humoral Response

Abstract: Summary Passive immunization (PI) with external antibodies has been used classically for rapid but temporary alleviation of disease. Transcending this role, recent studies have shown PI to induce lasting improvements in natural antibody production, suggesting that PI could become a powerful tool to engineer humoral responses. We propose a mechanism with which PI can alter the humoral response. Antigen-specific B cells evolve and get selected in germinal centers (GCs) on the basis of their ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 78 publications
6
72
0
Order By: Relevance
“…Following the observation of Nishimura et al [10] that there was no significant generation of anti-gp120 Abs in controllers, we ignored the ability of bNAbs to upregulate the humoral response [52,53]. Our study is thus conservative in its assessment of the influence of bNAbs.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Following the observation of Nishimura et al [10] that there was no significant generation of anti-gp120 Abs in controllers, we ignored the ability of bNAbs to upregulate the humoral response [52,53]. Our study is thus conservative in its assessment of the influence of bNAbs.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…bNAbs are known to engage the immune system via multiple mechanisms [20,87,[89][90][91]. The result could be heightened activation, which for HIV-1 infection, could mean greater susceptibility of target CD4 T cells.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Furthermore, the blunting effect noted has not been comprehensively defined, with a gap in our understanding of the impact of maternal antibody on qualitative or functional infant humoral immunity. Pre-existing antibodies have been shown to induce higher affinity humoral responses, possibly explained by competitive binding in the germinal center (GC) and/or a boost in uptake and antigen presentation, mediated by immune complexes in a Fc glycosylation-dependent manner (Zhang et al, 2013;Lofano et al, 2018;Garg et al, 2019;Langel et al, 2020). Most recently, a randomized control trial in Thailand (NCT02408926) studied term infants who were immunized with either acellular (aP)-or whole cell (wP) pertussis vaccines in infancy; results showed that infants born to women vaccinated in pregnancy had reduced pertussis-specific titres.…”
Section: Once Transferred What Do We Know About the Effect Of Maternmentioning
confidence: 99%